Experiential learning to increase palliative care competence among the Indigenous workforce: an Australian experience. Issue 2 (20th January 2018) - Shahid, Shaouli; Ekberg, Stuart; Holloway, Michele; Jacka, Catherine; Yates, Patsy; Garvey, Gail; Thompson, Sandra C
Abstract : Objectives: Improving Indigenous people's access to palliative care requires a health workforce with appropriate knowledge and skills to respond to end-of-life (EOL) issues. The Indigenous component of the Program of Experience in the Palliative Approach (PEPA) includes opportunities for Indigenous health practitioners to develop skills in the palliative approach by undertaking a supervised clinical placement of up to 5 days within specialist palliative care services. This paper presents the evaluative findings of the components of an experiential learning programme and considers the broader implications for delivery of successful palliative care education programme for Indigenous people. Methods: Semistructured interviews were conducted with PEPA staff and Indigenous PEPA participants. Interviews were recorded, transcribed and key themes identified. Results: Participants reported that placements increased their confidence about engaging in conversations about EOL care and facilitated relationships and ongoing work collaboration with palliative care services. Management support was critical and placements undertaken in settings which had more experience caring for Indigenous people were preferred. Better engagement occurred where the programme included Indigenous staffing and leadership and where preplacement and postplacement preparation and mentoring were provided. Opportunities for programme improvement included building on existing postplacement and follow-up activities. Conclusions: A culturally respectful experiential learning education programme has the potential to upskill Indigenous health practitioners in EOL care.